The Arabidopsis SR45 splicing factor bridges the splicing machinery and the exon-exon junction complex - Fanara, Steven (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.